Perceived service quality and customer loyalty in retail banking in Kenya - Auka, Daniel .O; Bosire, Joseph N.; Matern, Victor (European Centre for Research Training and Development UK, 2013)
The main aim of this study is to examine the effect of service quality dimensions on customer loyalty to the providers of retail banking services. It investigates the relationship between service quality dimensions and customer loyalty. To achieve this purpose, data was collected from a sample of 384 current customers of commercial banks on the five dimensions of service delivery: tangibility, reliability, responsiveness, assurance and empathy. The results indicate that all the dimensions of service quality have a positive and significant influence on customer loyalty in retail banking .This finding reinforces the need for bank managers to place an emphasis on the underlying dimensions of service quality in order to create and maintain customer loyalty
Keywords: Assurance; Customer Loyalty; Empathy; Reliability; Responsiveness; Service Quality; Tangibility